THE EFFECT OF SCREEN TEXT IN IMPROVING STUDENTS’ READING RATE AND READING COMPREHENSION: EFFECT OF SCREEN TEXT IN IMPROVING STUDENTS’ READING RATE AND READING COMPREHENSION - trisiliadevana (Universitas Jambi, 2019)
Reading comprehension is a complex process, it does not happen automatically. The process of comprehension begins when the reader encounters some new content, working memory is activated in order to capture the information already stored in long-term memory. Among some factors that influence students’ reading difficulties are low prior knowledge, lack of vocabulary and rate or fluency in reading. The reader is really required to consistent in maintaining reading rate of the text understanding and focus attention or concentrate fully on reading in order to understand the discourse content as a whole. In increasing the students’ reading ability, technology can be used as teaching tool. They are computer, mobile phone, tablet, or LCD. It has a big influence in education especially teaching reading. Most of students have experience reading a text from those technologies, or it can be said reading a text on screen, in their daily life. Therefore the objectives of this research was conducted to know the effect of using screen text in improving the students’ reading rate and reading comprehension. The population is students at English Education Study Program of Baturaja Univesity in academic year 2018/2019 and 36 students as sample. The research method was pre-experimental design, with pre-test and post-test, which to know the improvement after giving the treatment. Tests were used in collecting the data, silent reading rate test and reading comprehension test. Based on the result, it found that screen text have not only affected students’ reading rate but also comprehension.